Development of GIS spatial models on critical place needed of Malaysia Sign Language (MSL) for Persons with Disabilities (PWDS) deaf in Terengganu, Malaysia - Mohd Nawawi, Naimie; Kamarudin, Mohd Khairul Amri; Abu Samah, Mohd Armi; Loh, Ing Hoe; Toriman, Mohd Ekhwan; Mohamad, Lukman @ Zawawi; Abu Hassan, Mohd Syaiful Nizam (Trans Stellar, 2020)
Sign language is the priority of communication language between normal and deaf person. Usually normal person tries to communicate with the deaf but due to the absence of knowledge about the sing language making it difficult for them. Before getting a translator, deaf people have to do an appointment with sign language interpreter first. Then, looking at the public officer sector it is also one of the problems for deaf when they try communicating and making an appointment. At the abroad things like administration, religion or traffic signboard they already use the sign language for deaf to facilitate in daily life. The study will analyse the use and requirements of sign language in Terengganu. Geography Information System (GIS) aims to development the spatial models of critical place at Kuala Terengganu that really need a sign language. Before doing GIS Analysis, the study collected data about the percentage needed from respondent and coordinate of critical place in Kuala Terengganu. Respondents are the members of Terengganu Deaf Association will respond to the questionnaire. Based on the study, the regression findings show there are strong and significant between the two variables which is the use and requirements of sign language with value of R2 0.624 (62.4%). The researcher also found that there is positive relationship between these two variables. In the spatial models finding by GIS, Hospital Sultanah Nur Zahirah (HSNZ) had been selected as the main critical place that really need to use of sign language from the respondent. It is hoped that this finding can assist the government to apply in each place and at the same time can recover deaf person in social functionality.